Co-designing health promotion at a science centre: distributing expertise and granting modes of participation. Issue 2 (3rd April 2019) - Bønnelycke, Julie; Thiel Sandholdt, Catharina; Pernille Jespersen, Astrid
Abstract: Museums and science centres are increasingly employing participatory approaches to exhibition design. Despite the increasing interest, the dynamics, challenges and benefits of employing participatory methods in museum design remain under-researched. Ensuring that audiences are involved requires reflections on the aim of the participation, and on the implications of its practical and institutional embeddedness. We analyse how co-design frames the meeting between disciplinary fields, as well as achieving audience involvement, through the case of the PULSE project. Here, designers, researchers, and families co-designed a health-promoting exhibition at a Danish science centre. We investigate how the co-design process was shaped between the fields of health promotion research and exhibition design practice. We describe how audiences and professionals were redefined and repositioned, and how tensions arose and necessitated negotiations of expertise, authority and modes of participation. The ideal of visitor involvement created tensions with existing design and development practices complicating the translation of user experience into exhibition design.